A Helicobacter pylori Homolog of Eukaryotic Flotillin Is Involved in Cholesterol Accumulation, Epithelial Cell Responses and Host Colonization - Hutton, Melanie L.; D'Costa, Kimberley; Rossiter, Amanda E.; Wang, Lin; Turner, Lorinda; Steer, David L.; Masters, Seth L.; Croker, Ben A.; Kaparakis-Liaskos, Maria; Ferrero, Richard L. (Frontiers in Cellular and Infection Microbiology, 2017)
The human pathogen Helicobacter pylori acquires cholesterol from membrane raft domains in eukaryotic cells, commonly known as “lipid rafts.” Incorporation of this cholesterol into the H. pylori cell membrane allows the bacterium to avoid clearance by the host immune system and to resist the effects of antibiotics and antimicrobial peptides. The presence of cholesterol in H. pylori bacteria suggested that this pathogen may have cholesterol-enriched domains within its membrane. Consistent with this suggestion, we identified a hypothetical H. pylori protein (HP0248) with homology to the flotillin proteins normally found in the cholesterol-enriched domains of eukaryotic cells. As shown for eukaryotic flotillin proteins, HP0248 was detected in detergent-resistant membrane fractions of H. pylori. Importantly, H. pylori HP0248 mutants contained lower levels of cholesterol than wild-type bacteria (P < 0.01). HP0248 mutant bacteria also exhibited defects in type IV secretion functions, as indicated by reduced IL-8 responses and CagA translocation in epithelial cells (P < 0.05), and were less able to establish a chronic infection in mice than wild-type bacteria (P < 0.05). Thus, we have identified an H. pylori flotillin protein and shown its importance for bacterial virulence. Taken together, the data demonstrate important roles for H. pylori flotillin in host-pathogen interactions. We propose that H. pylori flotillin may be required for the organization of virulence proteins into membrane raft-like structures in this pathogen.